Thromboembolectomy in a Patient with Acute Arterial Occlusion in the Lower Limb and Complex Postoperative Evolution: Challenges in Emergency Hospital Practice - Guarachi, Juan Manuel Yampara; Rocha, Ana Paula de Carvalho Miranda Rosati; Habibe, Julia; Maillard, Noemi Fourcroy; Gaeta, Giovanna Jurcunas de Oliveira; da Silva, Felipe Ramon Menezes; Sant’anna, Pedro Gomes; Rodrigues, Carolina Lacerda; Rosati Rocha, Luis Fernando (Brazilian Journal of Case Reports, 2024)
We report the case of an elderly patient presenting with acute arterial occlusion of the lower limb, diagnosed and treated with emergency thromboembolectomy. The patient experienced postoperative complications, including reperfusion syndrome with acute kidney injury requiring dialysis support, as well as a urinary tract infection treated with antibiotic therapy. The clinical and laboratory evolution was closely monitored, culminating in discharge with recommendations for outpatient follow-up. This case highlights the challenges of managing acute arterial occlusions in elderly patients, focusing on complications associated with the procedure and prolonged hospitalization.